2022
DOI: 10.1021/acs.bioconjchem.2c00083
|View full text |Cite
|
Sign up to set email alerts
|

Cyanine Masking: A Strategy to Test Functional Group Effects on Antibody Conjugate Targeting

Abstract: Conjugates of small molecules and antibodies are broadly employed diagnostic and therapeutic agents. Appending a small molecule to an antibody often significantly impacts the properties of the resulting conjugate. Here, we detail a systematic study investigating the effect of various functional groups on the properties of antibody−fluorophore conjugates. This was done through the preparation and analysis of a series of masked heptamethine cyanines (CyMasks)-bearing amides with varied functional groups. These w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Therefore, we sought to introduce additional structural modifications. Our studies and others have found that careful balance and placement of charged functional groups significantly improve the properties of various targeted imaging agents. , In particular, our recent studies identified a first-generation FNIR-Tag, which contains an O -alkyl quaternary amine at the C4′ position and improves the tumor targeting of mAb and peptide conjugates. , Here, we explore placing additional charged functional groups adjacent to the polymethine chromophore. With this goal in mind, we designed FNIR-Tag-766 (Figure A), which contains both trimethyl-propyl ammonium indolenine substituents and a N -trimethyl-propyl-ammonium- N -butyl-sulfonate tertiary amide, which we used previously, at the 2-position of the C4′ aryl ring …”
Section: Cyanines For Protein-targeted Tumor Imagingmentioning
confidence: 99%
“…Therefore, we sought to introduce additional structural modifications. Our studies and others have found that careful balance and placement of charged functional groups significantly improve the properties of various targeted imaging agents. , In particular, our recent studies identified a first-generation FNIR-Tag, which contains an O -alkyl quaternary amine at the C4′ position and improves the tumor targeting of mAb and peptide conjugates. , Here, we explore placing additional charged functional groups adjacent to the polymethine chromophore. With this goal in mind, we designed FNIR-Tag-766 (Figure A), which contains both trimethyl-propyl ammonium indolenine substituents and a N -trimethyl-propyl-ammonium- N -butyl-sulfonate tertiary amide, which we used previously, at the 2-position of the C4′ aryl ring …”
Section: Cyanines For Protein-targeted Tumor Imagingmentioning
confidence: 99%
“…In contrast, asymmetric cyanines exhibit a larger Stokes shift with increased fluorescence intensity and brightness because of the unequal electron distribution, resulting in an altered excited state structure. 26–28 Analogous cyanine structures have already been used in haematology. 29…”
Section: Introductionmentioning
confidence: 99%
“…38 In contrast, asymmetric cyanines exhibit a larger Stokes shift with increased fluorescence intensity and brightness because of the unequal electron distribution, resulting in an altered excited state structure. [26][27][28] Analogous cyanine structures have already been used in haematology. 29 In spite of the fact that the relevance of cyanine conjugated antibodies is obviously high, recently, only a few examples have been published (Table S1 †).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have previously noted the influence of structure and charge on the pharmacokinetics of cyanine dyes and cyanine−antibody conjugates. 42,43 Further cellular imaging micrographs are given in the Supporting Information (Figures S44−S50). Also, the excitation−emission maps (EEMs) of the merocyanine 2 and the product of the MHI-148 oxidation, MHI-148-O, showed contrasting emission−excitation profiles when measured in PBS or 10% serum medium, as shown in Figure 5.…”
mentioning
confidence: 99%
“…The oxo form of the ubiquitous MHI-148 (the nonsulfonated analogous of compound 2 , MHI-148-O ) appears to be readily taken up by cancer cells even at 10 μM concentrations. Other authors have previously noted the influence of structure and charge on the pharmacokinetics of cyanine dyes and cyanine–antibody conjugates. , Further cellular imaging micrographs are given in the Supporting Information (Figures S44–S50).…”
mentioning
confidence: 99%